Assessment of genetic gains for grain yield and components from introgression of temperate donor inbred line into tropical elite maize inbred lines: II. Performance inter se - Musundire, L.; Derera, J.; Dari, S.; Tongoona, P. (Springer, 2021)
In maize breeding programs, temperate germplasm can be used to introgress genes from temperate inbred lines into elite tropical maize inbred lines to improve grain yield and its components across environments. This study's objective was to determine the genetic gains for grain yield and its components achieved by the introgression of temperate maize germplasm in tropical elite maize inbred lines for adaptability to South African environments. One hundred and twenty-two Introgressed inbred lines developed using the pedigree breeding method were crossed to four tropical elite inbred line testers using a line x tester mating design to obtain 488 experimental single cross hybrids. Subject to availability of adequate seed for evaluation, a panel of 444 experimental single-cross hybrids were evaluated using an augmented design in two experiments defined as populations A and B at three sites in South African environments. Grain yield and ear prolificacy had positive realized genetic gains of up to 58 and 26%, respectively, relative to the panel mean and commercial check hybrids. Secondary traits, such as anthesis and silking days, had gains ranging from 1 to 37%. Negligible gains were attained for stalk and root lodging and grain moisture content at harvest. Despite the need for further improvement, introgressed inbred lines performance inter se indicated significant grain yield potential improvements following one breeding cycle. The following experimental single-cross hybrids 12C22785, 12C20628, 11C1774, 12C20264, 12C20595, 11C1645 13XH349 outperformed the best commercial check hybrid PAN6Q445B, a leading hybrid on the South African market for grain yield performance potential. These seven selected single-cross hybrids also combined high grain yield potential performance with good ear prolificacy, in particular, experimental single-cross hybrids 12C20628, 11C1774 and 12C202595. Two experimental single-cross hybrids 12C2064 and 13XH349, combined high grain yield performance potential with low grain moisture content at harvest and improved standing ability relative to commercial check hybrids. Parents of these selected experimental single-cross hybrids will be advanced in the breeding program and will be the basis of future breeding for adaptation to South African environments. However, the general trend showed that many of the selected experimental single-cross hybrids did perform poorly for standability data depicted by plant aspects such as plant and ear height, stalk, and root lodging. Therefore, there is a need to improve these plants further to enhance the adaptability of tropical germplasm in South African environments. In conclusion, the introgression strategy effectively enhanced tropical elite inbred lines for the desired economic traits, to the extent that several of their combinations resulted in superior hybrids that are highly desired for South African markets.
Euphytica, Volume 217
Keywords: Maize hybrids; Genetic gain; Grain yield; Grain yield components; Performance inter se; Agriculture; University of Ghana